PENERAPAN METODE STORYTELLING DALAM PEMBELAJARAN SEJARAH ISLAM UNTUK MENINGKATKAN ANTUSIASME DAN DAYA INGAT SISWA DI MTSN 2 KABUPATEN BUNGO - Baili; Adilla, Ulfa; Ananda Agustina, Nadia; Saputri, Rahayu; Ayu Setianingsih, Fika; Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the application of the storytelling method in Islamic History learning to increase student enthusiasm and memory at MTsN 2 Bungo Regency. The background of this study stems from the low interest of students in Islamic History lessons, which are often delivered monotonously, resulting in students being less active and having difficulty remembering the material. The storytelling method is considered capable of creating an interactive and meaningful learning atmosphere through the power of stories in conveying historical and religious values. This study used a descriptive qualitative approach with a case study method. The research subjects were eighth-grade students, with data collection techniques through observation, interviews, and documentation. Data analysis was conducted thematically with a focus on increasing student enthusiasm and memory. The results of the study show that the application of storytelling has a positive impact on student learning motivation. Stories about Islamic figures delivered expressively are able to attract attention and build emotional involvement among students, making it easier for them to remember historical events. In conclusion, the storytelling method has been proven effective in improving the quality of Islamic History learning, especially in terms of student involvement and memory retention